2019
DOI: 10.1186/s13287-019-1226-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuronal survival, regeneration, and transient target reconnection after optic nerve crush and mesenchymal stem cell transplantation

Abstract: Background Retina and/or optic nerve injury may cause irreversible blindness, due to degeneration of retinal ganglion cells. We and others have previously shown that the intravitreal injection of mesenchymal stem cells (MSCs) protects injured retinal ganglion cells and stimulates their regeneration after optic nerve injury, but the long-term effects of this therapy are still unknown. Methods We injected rat MSC (rMSC) intravitreally in adult (3–5 months) Lister Hooded r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Here, we found that 14 days after optic nerve crush and vehicle injection, the number of Tuj1 + retinal neurons was dramatically reduced to 15.39% of the number in the control retina (1142 ± 49.46 Tuj1 + cells/mm 2 in control retinas; 117.8 ± 22.34 Tuj1 + cells/mm 2 in the vehicle group; Fig. 1 A, B, F), consistent with previous studies [ 5 , 6 , 8 , 31 , 50 ]. Treatment with hWJ-MSCs significantly increased RGC survival to 37.62% of the number in the control retina (429 ± 33.01 Tuj1 + cells/mm 2 in the hWJ-MSC group; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we found that 14 days after optic nerve crush and vehicle injection, the number of Tuj1 + retinal neurons was dramatically reduced to 15.39% of the number in the control retina (1142 ± 49.46 Tuj1 + cells/mm 2 in control retinas; 117.8 ± 22.34 Tuj1 + cells/mm 2 in the vehicle group; Fig. 1 A, B, F), consistent with previous studies [ 5 , 6 , 8 , 31 , 50 ]. Treatment with hWJ-MSCs significantly increased RGC survival to 37.62% of the number in the control retina (429 ± 33.01 Tuj1 + cells/mm 2 in the hWJ-MSC group; Fig.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies from our group have shown that cell therapy with adult bone marrow-derived mononuclear cells (BMMC) increases RGC survival in an optic nerve crush model for a short time period, and some axons can reach and establish synapses in the SC [ 8 , 30 ]. Alternatively, our group has shown that mesenchymal stem cells (MSCs) remain in the rat vitreous body for at least 18 weeks, providing prolonged neuroprotection to RGCs [ 6 ] and inducing strong axonal regeneration up to their brain targets [ 31 ]. Also, MSCs have been shown to protect RGCs in models of ischemia/reperfusion [ 32 ] and ocular hypertension [ 33 35 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when implanted in the injured region, beside differentiation and integration onto the damaged tissue, therapeutic effect of MSCs could be due to different mechanisms: secretion of neurotrophic factors [146], astroglial activation and neurogenesis induction [147], axon growth [148], enhancement of synaptic and cortical interhemispheric connections [149], immunomodulatory and anti-inflammatory properties [150], and decrease of apoptosis and oxidative stress [151]. Many cells types secrete exosomes as key players in cell-cell communication: exosomes contain many bioactive molecules and can regulate the expression of genes associated to neuronal development and transcription factors [152].…”
Section: Mesenchymal Stem Cells Potential In Neuronal Differentiationmentioning
confidence: 99%
“…In recent years, several studies have focused on the various therapeutic applications of mesenchymal stem cells (MSCs), including cell transplantation for cartilage and bone repair [1,2] and neuronal regeneration [3,4], due to their ability to self-renew and differentiate into a variety of cell types. Furthermore, due to their low immunogenicity and ability to secrete immune factors or cytokines [5,6], MSCs have been studied and utilized in clinical trials for some immune-related diseases, such as chronic graft versus host diseases (cGVHD) [7] and Crohn's disease [8].…”
Section: Introductionmentioning
confidence: 99%